An increase in BAG-1 by PD-L1 confers resistance to tyrosine kinase inhibitor in non–small cell lung cancer via persistent activation of ERK signalling. (November 2017) - Lin, Po-Lin; Wu, Tzu-Chin; Wu, De-Wei; Wang, Lee; Chen, Chi-Yi; Lee, Huei
Abstract: High programmed cell death 1 ligand 1 (PD-L1) expression in tumour tissues was associated with poor outcomes in non–small cell lung cancer (NSCLC) due to evasion of tumour immune surveillance. However, the role of PD-L1 in tumour invasion and resistance to tyrosine kinase inhibitor (TKI) treatments is not fully understood. Here, we provide evidence to support the involvement of PD-L1 expression in the invasiveness and TKI resistance in NSCLC cells by increased Bcl-2-associated athanogene-1 (BAG-1) expression. The upregulation of BAG-1 transcription by PD-L1 was verified by constructing the BAG-1 promoters using the polymerase chain reaction (PCR) and deletion mutations for luciferase reporter assays. The results indicated that C/EBPβ phosphorylation by extracellular signal-regulated kinase (ERK) signalling was responsible for PD-L1-mediated BAG-1 transcription. Mechanistically, the PD-L1-induced BAG-1 expression reciprocally increased PD-L1 expression due to persistent activation of ERK signalling, and it consequently conferred TKI resistance in NSCLC cells. The mechanistic action of this cell model was further confirmed by an animal model, affirming that PD-L1 conferred tumour invasiveness and TKI resistance via persistent activation of ERK signalling by the PD-L1/BAG-1 axis. We therefore suggest a combination of an ERK inhibitor with a TKI as a potential strategy for conquering PD-L1-mediated tumour invasion and TKI resistance in NSCLC patients whose tumours harbour high PD-L1/high BAG-1 expression. Highlights: Bcl-2-associated athanogene-1 (BAG-1) expression may be responsible for PD-L1-mediated tyrosine kinase inhibitor (TKI) resistance and cell invasion. Persistent activation of ERK signalling by the PD-L1/BAG-1 axis is responsible for PD-L1-mediated TKI resistance due to increased BIM protein instability. The combination of anti-PD-L1 monoclonal antibody (mAb) with gefitinib nearly completely suppresses tumour burdens induced by H1975 cells in nude mice. PD-L1, BAG-1, BIM and both combinations of PD-L1/BAG-1 and PD-L1/BIM show different associations with the response to TKI therapy in NSCLC patients. Anti-PD-L1 antibody immunotherapy may not only suppress tumour malignancy but may also overcome TKI resistance in high PD-L1-expressing NSCLC patients, particularly in patients whose tumours express PD-L1 + /BAG-1 + and PD-L1 + /BIM – combinations.